INCREASING MATHEMATICS LEARNING ACTIVITY AND OUTCOMES USING A CULTURALLY RESPONSIVE TEACHING APPROACH - Wiwit Yulianti; Darto Darto; Erni Widiyastuti; Gunawan Gunawan; Jaka Wijaya Kusuma; Winda Istanti (Yayasan Education and Social Center, 2026)
This study aims to determine the increase in activeness and learning outcomes using a culturally responsive teaching approach in grade III students of SD Negeri 3 Karangtengah. This research was carried out in 2 cycles, each cycle consisted of 2 meetings. Each meeting consists of 4 stages, namely planning, implementation, observation/observation, and reflection. The data analysis technique used in this study is a quantitative data analysis technique using tests and qualitative data analysis techniques through observation. The results of the classroom action research using the culturally responsive teaching approach were proven to improve student learning outcomes, where based on the test results showed that the percentage of classical completeness in the first cycle increased to 66.65 in the second cycle to 79.8. In addition, an increase also occurred in the percentage of student activity level in the first cycle reaching 49%, increasing in the second cycle to 59%.